Bullying in residential care for children: Qualitative findings from five European countries. (May 2019) - Mazzone, Angela; Nocentini, Annalaura; Menesini, Ersilia
Abstract: The present study addressed institutionalised children and staff members' perspectives about bullying in Residential Care settings (RCs) in five European countries (Bulgaria, France, Greece, Italy and Romania.). Interviews and focus groups were conducted respectively with 123 institutionalised children and adolescents (age range: 6–18) and staff members ( N = 95; age range: 23-63). Thematic analysis was adopted to analyse the data. Overall, findings indicated that participants were not fully aware of the specific features of bullying. Children and adolescents considered bullying as a normative behaviour and were reluctant to ask for adults' help when bullying happened. Staff members attributed bullying to children's traumatic experiences and to a need for adults' attention. Findings shed light on the lack of standardised protocols and of professional trainings to tackle bullying. Implications for intervention programs aimed at preventing and tackling bullying are discussed. Highlights: This study investigated children and staff members' understanding and experiences of bullying in RCs. Peer hierarchies and interchangeability of bullying roles were the main futures of bullying in RCs. Staff members viewed bullying as the result of children's traumatic experiences. Children mostly expressed their distrust in the anti-bullying measures adopted by the staff members. Overall, standardised protocols to deal with bullying were missing in all facilities involved in this study.